(untitled) (Annals of Medical Research, 2021)
Aim: The purpose of the study is to evaluate the effect of Oxidized Gelatin Sponge (OGS) usage in the donor site on pain during the post-operation period through the VAS form administered to the patients.Material and Methods: The study was carried out by using the VAS forms filled in on the 2nd and 7th days following the operation by the 34 patients who had undergone Free Gingival Graft (FGG) operation performed by the same periodontologist in the Faculty of Dentistry, Harran University, Turkey. The information on whether the wound that formed in the donor site was packed primarily and, if packed, what material was used was obtained from the periodontologist who treated the patients. As a result of these assessments, the patients whose donor sites were left to heal by secondary intention were categorized as the control group and those whose wounds were packed with OGS as the experimental group.Results: When the VAS scores of the 22 patients, 14 of whom were female and 8 males, were examined, no statistically significant difference between females and males was determined (p 0.05). While the 2nd and 7th day VAS value averages of the patients whose donor sites were left to heal by secondary intention were 5.71±0.88 and 2.82±0.62 respectively, these averages in the group whose donor sites were packed with OGS were determined to be 3.88±0.95 and 1.67±0.80 respectively. In addition, when the 2nd and 7th day VAS value averages of the two groups were compared, no statistically significant difference was found. Conclusion: It was concluded that packing the donor site with OGS following the FGG operations does not have an impact on the intensity of post-operation pain felt by the patients.